DEVELOPMENT AND EVALUATION OF POLYHERBAL GEL FOR ANTIFUNGAL ACTIVITY - A., UMADEVI; KUMARI, CHAMPA; KUMAR, P. AJITH; NASMIN AM, HAMEEMATH SHAMANA; K., DIVYA; V., HISANA P. (International Journal of Current Pharmaceutical Research, 2018)
Objective: Piper betal and Piper nigrumare traditional medicinal plants that have antifungal activity against Candida albicans, a combination of these two plants have not been known for its activity against this fungus. The purpose of this research was to formulate topical gel, a combination of P. betal and P. nigram which has antifungal activity against Candida albicans. Methods: The antifungal activity test of P. betal and P. nigrum using agar well diffusion method was carried out. Thereafter, a topical gel formulation was prepared using Sodium carboxymethyl cellulose as a gelling agent of concentration 1; 1.5 and 2%. Test parameters for topical gel includes organoleptic, pH, extrudability, spreadability, diffusion, and stability test. Result: The results of this study showed that P. betel and P. nigrum extracts had antifungal activity. Antifungal activity combination of P. betel and P. nigrum leaf extract is synergistic. For the formulation materials, the concentration chosen is 1: 1 (P. betel: P. nigrum) because in that combination the value of the resistor area is still categorized well. The stability test results stated that all the formulas were stable even after 30 d of stability studies. Conclusion: This is the first report on the scientific evaluation of betel and pepper leaf extracts combination as a gel for antifungal activity. Thus our study reveals both leaf extracts to be good antifungals; their methanolic hydro extracts may be formulated as hydrogels with satisfactory physicochemical parameters.